Recovery of the Traditional Cuisine of the Provinces of Alto Magdalena and Tequendama, Case of Municipalities of Agua de Dios, El Colegio, Girardot, Guataqui, Nilo and Tocaima of the Department of Cundinamarca, Colombia - Bernal Vásquez, Evalo Enrique
In this article project preliminary arises from the research currently carried out by professionals SENA CTPDE Girardot, research group supported by SENNOVA and COLCIENCIAS.The objective of this project is to recover the traditional food culture of the municipalities under study in the region of Alto Magdalena and region Tequendama (Guataquí, Girardot, Agua de Dios, Tocaima, Vereda Acuata, sidewalk El Colegio, sidewalk El Paraíso the High land of the ancient inhabitants Panches family Caribbean Indian tribes that inhabited this area in ancient time until the colony. All this study was conducted from an integration and socialization process with communities and their carriers traditional knowledge, this aim is to promote, rescue and to exalt the gastronomic know little known in the region, so that with this are recognized in the cultural and tourism sector level.It is important to show these dishes in a traditional way and in turn bring them to modern cooking presentations, respecting their methods of preparation and preserving their flavors, colors and other traditional organoleptic characteristics; presenting their social, cultural and historical origin which later will result in development with technology platforms such as nanotechnology.The methodology of this project is made based policies and methods required by the ministry of culture and tourism for the safeguarding of knowledge and intangible immemorial. To do field work was carried out, requesting permission to the offices of culture and municipal tourism, this in order to locate the niche carriers of knowledge gastronomic each place and make preparation practices (Mingas), designing standard recipes, technical specifications, supporting documents, videos and photos, to review evidence and information sources of gastronomic knowledge of each study area.